A solution processed carbon nanotube modified conducting paper sensor for cancer detection. Issue 48 (18th November 2015) - Kumar, Saurabh; Willander, Magnus; Sharma, Jai G.; Malhotra, Bansi D.
Abstract : A solution processed poly (3, 4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS)–carbon nanotube (CNT) nano-composite has been utilized for the fabrication of a smart conducting paper (CP) via dip coating. Abstract : A solution processed poly(3, 4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS)–carbon nanotube (CNT) nano-composite has been utilized for the fabrication of a conducting paper (CP) via dip coating. Further, high conductivity of this paper (from ∼6.5 × 10 −4 to 2.2 × 10 −2 S cm −1 ) obtained by treating it with formic acid (CNT/FA@CP) is due to the removal of the non-conducting PSS molecules from its surface. This smart conducting platform has been used for the conjugation of the anti-carcinoembronic antigen (CEA) protein for quantitative estimation of CEA, a cancer biomarker. Transmission electron microscopy (TEM), Raman spectroscopy, X-ray diffraction (XRD), scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), electrochemical impedance spectroscopy (EIS) and amperometric techniques have been used to characterize the low cost, flexible and environmentally friendly conducting BSA/anti-CEA/CNT/FA@CP) paper electrode that is found to be highly sensitive (7.8 μA ng −1 ml cm −2 ) in the physiological range (2–15 ng ml −1 ) of CEA. The response of the paper electrode is validated using CEA concentration of serum samples of cancer patients obtained via the immunoassay technique.